Rethinking pedagogy for a digital age : designing for 21st century learning. - Beetham, Helen;Sharpe, Rhona (New York : Routledge Taylor & Francis Group, 2013)
Through a critical discussion of the issues surrounding the design, sharing and reuse of learning activities, the second edition of Rethinking Pedagogy for a Digital Age examines a wide range of perspectives on effectively designing and delivering learning activities to ensure that future development is pedagogically sound, learner-focused, and accessible. This powerful book: examines the reality of design in practice, shares tools and resources to guide practice, analyses design within complex systems, discusses the influence of open resources on design, includes design principles for mobile learning, explores practitioner development in course teams and presents scenarios for design for learning in an uncertain future. Illustrated by case studies from across disciplines and supported by a helpful appendix of tools and resources for researchers, practitioners and teachers, the second edition of Rethinking Pedagogy for a Digital Age is an essential guide to designing for 21st Century learning.
Part 1. Principles and practices of designing -- 1. Technology-enhanced learning: the role of theory -- 2. Designing for active learning in technology-rich contexts -- 3. The analysis of complex learning environments -- 4. The challenge of teachers' design practice -- 5. Tools and resources to guide practice -- 6. Describing ICT-based learning designs that promote quality learning outcomes -- 7. Learning designs as a stimulus and support for teachers' design practices -- 8. Representing practitioner experiences through learning designs and patterns -- 9. The influence of open resources on design practice -- Part 2. Designing for learning in context -- 10. Designing for learning in course teams -- 11. The art of design -- 12. Activity designs for professional learning -- 13. Designing for practice: a view from social science -- 14. Student as producer is hacking the university -- 15. The LAMS community: building communities of designers -- 16. Design principles for mobile learning -- 17. Designing for learning in an uncertain future.
Includes bibliographical references and index.
Keywords: COMPUTER-ASSISTED INSTRUCTION -- CURRICULA -- PLANNING